Differential diagnosis of neonatal jaundice - I. N. Zakharova; A. N. Goryainova; I. N. Kholodova; I. D. Мaikova; E. V. Belenovich; E. V. Tambieva; E. V. Bolbikova; A. N. Melen'kina; A. A. Khudyakov (Медицинский совет, 2016)
Jaundice is one of the most common symptoms of the neonatal period which in most cases is not associated with a serious illness. For example, jaundice in healthy newborns which does not affect the child's development. Nevertheless, in 2% of cases the causes of jaundice should be investigated, especially if it is long-term and extends beyond the neonatal period. Underestimating the history and late examination lead to diagnostic errors which sometimes cannot be corrected. The risk of direct hyperbilirubinemia should be taken into account which may be caused by malformations of the biliary tract development or other congenital and acquired diseases of the hepatobiliary system, for the treatment of which cholagogues can be successfully used. The prognosis for the biliary tract anomalies is directly related to the promptness of diagnosis and surgery. Understanding the difference between direct and indirect hyperbilirubinemia in infants is necessary for timely examination and treatment of the infant.